SURVIVAL ANALYSIS OF LONG-TERM SURVIVORSHIP OF HIV PATIENTS UNDER ANTIRETROVIRAL THERAPY AT GENERAL HOSPITAL, UGBA, BENUE STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2025)
Survival model plays a vital role in the understanding of prognosis and hence management of diseases. In this study, the long-term survival of HIV/AIDS patients under antiretroviral therapy (ART) is evaluated using Survival models. In particular, the Kaplan-Meier Estimator was used to estimate the Long-term survival of HIV/AIDS patients under ART. A retrospective data was obtained on HIV/AIDS patients who enrolled on ART at General Hospital, Ugba Logo Local Government Area, Benue state, Nigeria from year 2018 to 2022 for the study. Results revealed that 96% of HIV/AIDS patients under antiretroviral therapy had suppressed viral load for at least 8.8 years. Further test on the equality of survival distributions of female and male gender based on the Log-Rank, Breslow (generalized Wilcoxon) and Tarone-Ware statistic revealed that the survival distributions of the female and male patients are similar at 0.05 level of significance. It is recommended that people living with HIV/AIDS should accept antiretroviral therapy so that they could live healthy lives.
Keywords: Survival Analysis; Kaplan-Meier Estimator; HIV/AIDS; Antiretroviral Therapy